Achieving Ultrahigh Output Energy Density of Triboelectric Nanogenerators in High‐Pressure Gas Environment. Issue 24 (17th November 2020) - Fu, Jingjing; Xu, Guoqiang; Li, Changheng; Xia, Xin; Guan, Dong; Li, Jian; Huang, Zhengyong; Zi, Yunlong
Abstract: Through years of development, the triboelectric nanogenerator (TENG) has been demonstrated as a burgeoning efficient energy harvester. Plenty of efforts have been devoted to further improving the electric output performance through material/surface optimization, ion implantation or the external electric circuit. However, all these methods cannot break through the fundamental limitation brought by the inevitable electrical breakdown effect, and thus the output energy density is restricted. Here, a method for enhancing the threshold output energy density of TENGs is proposed by suppressing the breakdown effects in the high‐pressure gas environment. With that, the output energy density of the contact‐separation mode TENG can be increased by over 25 times in 10 atm than that in the atmosphere, and that of the freestanding sliding TENG can also achieve over 5 times increase in 6 atm. This research demonstrates the excellent suppression effect of the electric breakdown brought by the high‐pressure gas environment, which may provide a practical and effective technological route to promote the output performance of TENGs. Abstract : As an emerging high‐efficiency energy harvester, the output performance of the triboelectric nanogenerator (TENG) was limited by the inevitable electrical breakdown effect. A method for suppressing the breakdown effect in the high‐pressure gas environment is proposed here, which may provide a practical and effective technological route to promote the output performance of TENGs.